Hybrid Numerical–Experimental Strategy for Damage Characterization of Sae 1045 Steel - Garcia-Herrera, C; Toro-Campos, S; Toro-Campos, S; Aranda-Acuna, P (Elsevier Ltd, 2024)
In this work, the elastoplastic behavior with continuous mechanical damage in a SAE 1045 steel is characterized using mainly torsional tests and simulations. A numerical–experimental inverse analysis procedure is proposed to fit a von Mises-type elastoplastic model and a Lemaitre-type continuous damage model to the material s mechanical response obtained in torsional tests. A FEM simulation campaign is carried out to calibrate the damage model, considering a two-step linear evolution of the damage variable in terms of the degradation of the elastic torsional stiffness measured in cyclic torsional tests. The procedure is validated with a numerical–experimental comparison in tensile tests to demonstrate the validity of the solution in other loading paths. The numerical model obtained is used to analyze the local effects of the damage and its distribution in torsional and tensile tests. © 2023 Elsevier Masson SAS